PEMBERDAYAAN MASYARAKAT DALAM PENGEMBANGAN PENDIDIKAN KARAKTER REMAJA ISLAM DI PRINGU BULULAWANG MALANG - Nurhalimah, Evi (INTAJ, 2018)
The concern of the nation that is experiencing crises in various aspects of life makes the role of education especially in schools questionable. However, it can not be assessed so because in realizing the purpose of education in addition to the role of the school there is also the role of family and society. Pringu Bululawang Malang is a village with a majority of the Moslem population, but they still have not done their duty as Moslem well. Along with the development of Islam in Pringu, this condition began to change marked by the emergence of awareness of carrying out obligations as Moslem. This development can be seen, among others, by the existence of various Islamic educational activities implemented to develop the character of Islamic teenagers there. Leaders and community leaders, as well as citizens of the community, seemed enthusiastic to support and develop the education of youth Islamic character there. The result of the research found that; (1) the community empowerment mapping strategy undertaken is area mapping, problems, potential, infrastructure suggestions, and character education; (2) community empowerment planning strategy that is carried out is the formation of the board, the formulation of the problem handling program, the exploration of empowerment potential, the utilization of village facilities and the house of the citizens, the inculcation of character education value; (3) management strategy undertaken is routine meetings, socialization of the program, making the community as a source of development, utilization of village facilities, the inculcation of character values through religious and social activities. Keywords: Community Empowerment, Education Development, Character